2017
DOI: 10.1007/s11356-017-8960-2
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of distiller’s dried grains with solubles (DDGS) in layer diets affect the nutrients digestibility and manure pollution by nitrogen and phosphorous?

Abstract: The objective of the current study was to examine the effect of the inclusion levels of distiller's dried grains with solubles (DDGS) which partially and fully replaced soybean meal (SBM) in laying hen diets with or without enzyme or vitamin E supplementation on nutrients digestibility and excreted nitrogen and phosphorous. For these purposes, a total of 180 Hisex Brown laying hens at 22 weeks of age were randomly distributed into 15 treatment groups in a 5 × 3 factorial design experiment including five levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Multi-enzyme supplementation may improve the nutrients apparent digestibility by lowering the viscosity of digesta and improving nutrients digestion and absorption [54]. Enzymes also increase the solubilization and disruption of feed endosperm cell wall, which positively reflects on nutrients digestibility as documented by Patterson and Aman [55] and Abd El-Hack et al [56]. On the other hand, Shalash et al [32] found that digestibility of crude protein, ether extract, crude fibers, and nitrogen-free extract were not statistically impacted by multi-enzyme supplementation in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-enzyme supplementation may improve the nutrients apparent digestibility by lowering the viscosity of digesta and improving nutrients digestion and absorption [54]. Enzymes also increase the solubilization and disruption of feed endosperm cell wall, which positively reflects on nutrients digestibility as documented by Patterson and Aman [55] and Abd El-Hack et al [56]. On the other hand, Shalash et al [32] found that digestibility of crude protein, ether extract, crude fibers, and nitrogen-free extract were not statistically impacted by multi-enzyme supplementation in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Increased feed costs and limited amounts of animal protein sources in poultry feed have led to the use of alternative plant proteins that make up some or all animal protein in feed (El Boushy et al, 2000;Vasso & Russ, 2007). Therefore, considerable attention has been given to the use of unconventional feedstuffs, such as agro-industrial by-products, in the formulation of poultry diets, with the intention of achieving suitable utilization and economic efficiency of poultry production (Alagawany et al, 2015;Abd El-Hack et al, 2017a;2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Results of the present work demonstrated that extra protein consumed by birds could not be productively utilized by ostrich chicks and were probably eliminated via fecal nitrogen as reported in previous publications (Ahmed et al 2011, Mahrose et al 2015. However, Bovera et al (2011) claimed that feed containing 17% CP was optimum for ostrich chicks at 20 weeks of age and feeding growing ostriches on higher protein levels not only wasteful but also pollute the environment through the excretion of more unutilized nitrogen (Abd el-Hack et al 2017. Due to these explanations, growth rate of the ostriches appeared to be influenced by other environmental factors (Deeming and Ayres 1993), such as stocking density.…”
Section: Discussionmentioning
confidence: 99%